(-9)-2+(-6)-(-8) simplify step by step
Answers
Answered by
1
The value of the expression (-9)-2+(-6)-(-8) is -9
Step-by-step explanation:
Given:
expression = (-9)-2+(-6)-(-8)
To find:
simplify the expression
Solution:
We use the BODMAS rule here
Thus, all the additions will be performed first, and later the subtractions
(-9)-2+(-6)-(-8)
= -11 + (-6)-(-8) .................[after adding the numbers (-9) & (-2)]
= -11 + (-6) + 8 .........................[operating on the second bracket]
= -11 + (2).................[positive and negative means subtraction]
= -9
∴ (-9)-2+(-6)-(-8) = -9
Thus, the value of the expression (-9)-2+(-6)-(-8) is -9
#SPJ2
Similar questions